Dancing with the enemy: symbiotic relationships between plant RNA viruses and their hosts - Roy, Abhisha; Bhattacharjee, Bipasha; Hallan, Vipin (Frontiers in Plant Science, 2025)
While many plant viruses cause diseases that reduce crop yield, quality, and overall plant health, not all viruses are purely detrimental. Under certain conditions, some can confer beneficial effects, including improving abiotic stress tolerance, enhancing immunity, or even increasing pollination efficiency. RNA viruses, though most often associated with disease, can also establish symbiotic relationships with their hosts that are mutualistic, commensal, or conditionally beneficial depending on environmental factors. This mini-review summarizes how mild viral infections can protect plants against more severe pathogens (cross-protection), induce signaling and epigenetic changes that enhance stress tolerance, and serve as tools for gene delivery and crop improvement. Collectively, these findings underscore the potential of RNA viruses to support plant adaptation and survival, offering innovative possibilities for sustainable agriculture and climate resilience.